KEPRIBADIAN TOKOH DALAM CERPEN ASY’AB FĪ BILĀDI WAQ WAQ 2002) DAN ASY’AB FĪ MINCHAH (2002) KARYA WAJĪH YA’QUB AS-SAYYID: KAJIAN PSIKOLOGI SASTRA SIGMUND FREUD - Nurul Khoidah, Afnan Arumi (CMES (Center of Middle Eastern Studies), 2016)
This article aims to explain the structural text of Asy'ab fī Bilādil Wāq Wāq (2002) and Asy'ab fī Michnah (2002) by Wajī h Ya'qub As-Sayyid by using Burhan Nurgiyantoro‟s structural theory. So, The purpose of this study focused to describes the structural text of both. The results shows that: first, The text structure in the short story Asy'ab fī Bilādil Wāq Wāq (2002) and Asy'ab fī Michnah (2002) is built with 6 (six) elements. Second, The characters in the short story of both text  are categorized into two :Protagonist and antagonist. (1) the protagonist is represented by the figure: (a) Asy'ab with a number of personalities such: Wise, patient, trustworthy, responsible, broad-minded, hard work, humble and calm; (b) Great chef with his personality: Care for others and firm; (c) servants with his personality: Honest and submissive; (d) friends with personality: Likes to help and care for others; (e) Asy'ab's wife with her personality: Care for her husband, (2) the antagonist is represented by a character: (a) Governor with a number of personalities: hunatic, emotional and greedy; (b) Minister with a number of personalities: Evil, stubborn, nonchalant and greedy.